N-terminal-pro-brain natriuretic peptide is decreased in insulin dependent gestational diabetes mellitus: a prospective cohort trial - Gottsauner-Wolf Michael (Cardiovascular Diabetology, 2011)
Abstract Background N-terminal-pro-brain natriuretic peptide (NT-proBNP) is elevated in gestational hypertension and preeclampsia. This trial aimed to generate data for gestational diabetes mellitus patients, who are at risk to develop these complications. Methods We have measured NT-proBNP in 223 otherwise healthy women between gestational week 24 and 32 referred to the outpatient diabetes unit in a cross-sectional study. Results 88 control subjects, 45 patients with indication for medical nutrition therapy (MNT) alone and 90 patients who required insulin therapy were included. Groups of women were comparable regarding gestational week. Body mass index before pregnancy and at blood draw was significantly higher in subjects with insulin dependent gestational diabetes mellitus compared to MNT controlled gestational diabetes mellitus. NT-proBNP was significantly lower in patients with insulin dependent gestational diabetes mellitus (35 ± 25 pg/ml) compared to controls (53 ± 43 pg/ml, p = 0.012). Conclusions NT-proBNP is within the reference range of normal subjects in women with gestational diabetes mellitus. Differences in body mass index, changes in glomerular filtration rate and haemodynamics may explain lower NT-proBNP concentrations in insulin dependent gestational diabetes mellitus. A false negative interpretation needs to be considered in these women.